TNFRSF11B-modified umbilical cord mesenchymal stem cells as a novel strategy for bone-related diseases by suppressing osteoclast activity - Mina Ding; Qian Ding; Zhijie Liu; Liang Wang; Ke Pei; Junyuan Hu; Yan Liao; Jian V. Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Background and objective Mesenchymal stem cells (MSCs), possessing multilineage potential, are capable of differentiating into osteoblasts and thus serve as suitable seed cells for bone regeneration. Tumor necrosis factor receptor superfamily member 11B (TNFRSF11B) gene encodes osteoprotegerin (OPG), which has a critical role in repressing osteoclast differentiation and has been reported to influence the adipogenic differentiation of bone marrow mesenchymal stem cells (BMMSCs). Nevertheless, the impact of TNFRSF11B on the osteogenic differentiation of umbilical cord mesenchymal stem cells (UCMSCs) remains unclear. This study aimed to investigate the role of TNFRSF11B in the osteogenesis of UCMSCs and bone remodeling. Methods Differentially expressed genes (DEGs) were identified from the GEO database using R software. TNFRSF11B was transduced into UCMSCs by a lentiviral vector. Cell differentiation capacity was assessed by ALP staining, TRAP staining, and qRT-PCR assay. Proteomic analysis was performed to investigate the key proteins in TNFRSF11B-OE-UCMSCs that inhibit osteoclast differentiation. Results We found that the TNFRSF11B gene was upregulated during osteogenic differentiation and downregulated during adipogenic differentiation of UCMSCs. UCMSCs overexpressing the TNFRSF11B gene were successfully generated via lentivirus transfection. However, neither the overexpression of TNFRSF11B nor treatment with exogenous OPG protein was sufficient to enhance the osteogenic potential of UCMSCs in vitro. Conditioned medium from TNFRSF11B-overexpressing UCMSCs significantly suppressed RANKL-induced osteoclast differentiation, while no significant effect was observed on osteoblast differentiation compared to the control group. Proteome analysis revealed that in the TNFRSF11B-OE-CM group, the expression of C1R, MDH1, and ACLY was significantly downregulated, while the expression of FETUB and METRNL was upregulated in the TNFRSF11B-OE-CM group, which was associated with the inhibition of osteoclast differentiation. Conclusion This study demonstrates that although TNFRSF11B overexpression does not promote osteogenesis in UCMSCs, it may participate in regulating bone remodeling by inhibiting osteoclast differentiation.